2020
DOI: 10.1161/circ.141.suppl_1.02
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 02: Brain Regions Activation During Stress and Accelerated Biological Aging

Abstract: Background: Psychological stress is a risk factor for major adverse cardiovascular events in individuals with coronary artery disease (CAD). Accelerated biological aging, as indicated by telomere shortening, is a recognized pathway by which stress may lead to cardiovascular disease incidence and mortality. We sought to investigate brain correlates of acute psychological stress and short telomeres in men and women with CAD. Methods: Individuals with CAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Both the magnitude of PC mobilization with mental stress and the change in SDF1 level induced by mental stress were independent predictors of adverse incident cardiovascular events. Finally, we found that activation of specific brain areas during mental stress involved in executive function, stress activation and the limbic system were associated with greater mobilization of progenitor cells [86] as well as with worse cardiovascular outcomes [18].…”
Section: Prognostic Value Of Mental Stress-induced Vascular Perturbationsmentioning
confidence: 78%
“…Both the magnitude of PC mobilization with mental stress and the change in SDF1 level induced by mental stress were independent predictors of adverse incident cardiovascular events. Finally, we found that activation of specific brain areas during mental stress involved in executive function, stress activation and the limbic system were associated with greater mobilization of progenitor cells [86] as well as with worse cardiovascular outcomes [18].…”
Section: Prognostic Value Of Mental Stress-induced Vascular Perturbationsmentioning
confidence: 78%